Uplisting of Malagasy precious woods critical for their survival. (July 2019) - Waeber, Patrick O.; Schuurman, Derek; Ramamonjisoa, Bruno; Langrand, Marion; Barber, Charles V.; Innes, John L.; Lowry, Porter P.; Wilmé, Lucienne
Abstract: Illegal timber trade is a global issue; highly prized rosewoods are mainly sourced from Africa and Madagascar. In Madagascar, where corruption and political instability are rampant, forest regulations have been issued during the last 15 years to facilitate illegal rosewood exploitation. The current situation precludes non-detriment findings (under which the exporting State ensures that a proposed action will not be detrimental to the survival of a species) intended to enable sustainable use of standing populations, but the Malagasy government, backed by the World Bank, is promoting the sale of massive stocks of confiscated precious wood. We argue that allowing the sale of these stocks would encourage further illegal harvest. No suitable tools are available to identify, control or monitor standing trees or cut timber, and there are substantial knowledge gaps regarding species limits, population sizes, distribution and abundance. When combined with taxonomic confusion and weak governance, these factors necessitate uplifting all of Madagascar's precious woods to Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES).